Resilience of People with Disabilities Who Have Experienced Bullying - Amara Laili Zumarotul Zahro; Ira Darmawanti (Character Jurnal Penelitian Psikologi, 2023)
People with physical disabilities often get bullied because of their physical limitations, which makes them feel down. The existence of this makes resilience skills important to have so that they are able to rise from the adversity experienced. This study aims to determine the description of resilience and sources of resilience in disabled people who have experienced bullying. This study uses a case study approach and focuses on two disabled participants aged 22 years who have experienced bullying. The data collection technique used was semi-structured interviews and thematic data analysis techniques. This study produced two themes, namely the description of resilience and the sources of resilience possessed by the two participants. The results of this study resulted that both participants had aspects of resilience consisting of emotional regulation, optimism, impulse control, causal analysis, self-efficacy, empathy and reaching out. The two participants also had sources of resilience which included inner strength, external support, interpersonal skills and problem solving that supported the two participants to rise from adversity caused by bullying they had experienced.